Anomalous Left Coronary Artery From the Pulmonary Artery Presenting as Dilated Cardiomyopathy With Regional Wall Motion Abnormality on Point-of-Care Ultrasound. Issue 7 (July 2019) - Shaahinfar, Ashkon; Ghazi-Askar, Zahra M.; Siroker, Hannah; Nagdev, Arun
Abstract : Abstract: Anomalous left coronary artery from the pulmonary artery is a rare cause of dilated cardiomyopathy. We present the first reported case of anomalous left coronary artery from the pulmonary artery diagnosed by point-of-care ultrasound, leading to expedited management, stabilization, and eventual treatment. Abstract : Supplemental digital content is available in the text.